Organ-specific electrophile responsivity mapping in live C. elegans - Liu, Jinmin; Kulkarni, Amogh; Gao, Yong-Qi; Urul, Daniel A; Hamelin, Romain; Novotny, Balázs Á; Long, Marcus J C; Aye, Yimon (Cell, 2024)
Proximity labeling technologies are limited to indexing localized protein residents. Such data-although valuable-cannot inform on small-molecule responsivity of local residents. We here bridge this gap by demonstrating in live C. elegans how electrophile-sensing propensity in specific organs can be quantitatively mapped and ranked. Using this method, >70% of tissue-specific responders exhibit electrophile responsivity, independent of tissue-specific abundance. One responder, cyp-33e1-for which both human and worm orthologs are electrophile responsive-marshals stress-dependent gut functions, despite manifesting uniform abundance across all tissues studied. Cyp-33e1's localized electrophile responsivity operates site specifically, triggering multifaceted responses: electrophile sensing through the catalytic-site cysteine results in partitioning between enzyme inhibition and localized production of a critical metabolite that governs global lipid availability, whereas rapid dual-cysteine site-specific sensing modulates gut homeostasis. Beyond pinpointing chemical actionability within local proteomes, organ-specific electrophile responsivity mapping illuminates otherwise intractable locale-specific metabolite signaling and stress response programs influencing organ-specific decision-making.